2019
DOI: 10.3390/electronics8050487
|View full text |Cite
|
Sign up to set email alerts
|

A High-Efficiency K-band MMIC Linear Amplifier Using Diode Compensation

Abstract: This paper describes the design and measured performance of a high-efficiency and linearity-enhanced K-band MMIC amplifier fabricated with a 0.15 μm GaAs pHEMT processing technology. The linearization enhancement method utilizing a parallel nonlinear capacitance compensation diode was analyzed and verified. The three-stage MMIC operating at 20–22 GHz obtained an improved third-order intermodulation ratio (IM3) of 20 dBc at a 27 dBm per carrier output power while demonstrating higher than a 27 dB small signal g… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 13 publications
0
2
0
Order By: Relevance
“…Two different kinds of mmWave amplifiers are presented in two contributions. The design of a high-efficiency K-band MMIC linear amplifier using diode compensation is presented by Zhu and co-workers [6] together with its measured performance, while in a study by Doo and colleagues [7] a broadband mmWave waveguide package, which covers the entire W-band (75-110 GHz), is presented and applied to build a low noise amplifier module. This module measures gains greater than 14.9 dB from 75 GHz to 105 GHz (12.9 dB at the entire W-band) and noise figures less than 4.4 dB from 93.5 GHz to 94.5 GHz.…”
Section: Contributions In This Special Issuementioning
confidence: 99%
“…Two different kinds of mmWave amplifiers are presented in two contributions. The design of a high-efficiency K-band MMIC linear amplifier using diode compensation is presented by Zhu and co-workers [6] together with its measured performance, while in a study by Doo and colleagues [7] a broadband mmWave waveguide package, which covers the entire W-band (75-110 GHz), is presented and applied to build a low noise amplifier module. This module measures gains greater than 14.9 dB from 75 GHz to 105 GHz (12.9 dB at the entire W-band) and noise figures less than 4.4 dB from 93.5 GHz to 94.5 GHz.…”
Section: Contributions In This Special Issuementioning
confidence: 99%
“…Recent studies have demonstrated different realization forms of power amplifier MMICs for K-band transmitters, such as the 21-23 GHz GaN Doherty PA, 1 linear PAs, 2-3 and 18.5-24 GHz GaN on Si, GaN on SiC MMIC PA, 4 and a large number of GaAs MMIC PAs with different gate length processes. [5][6][7][8] In these studies, most of the MMIC designs are produced using a conventional design procedure and only consider the matching from a certain point of view, such as high efficiency or broadband. In this paper, an improved MN design procedure for MMIC PA capable of covering the entire downlink operating frequency band is proposed.…”
Section: Introductionmentioning
confidence: 99%